MAIN DIRECTIONS OF APPLIED KIRLIANOGRAPHY IN ECOLOGY AND MEDICINE - Mintser, O. P.; Pisotska, L. A.; Glukhova, N. V. (Medical Informatics and Engineering, 2020)
Background. The methods of express diagnostics of the energy-informational status of any environmental object are investigated. It is shown that approaches based on visualization of a gas-discharge glow around objects of animate and inanimate nature in a high-voltage field, known in the world as the Kirlian effect, are effective. Materials and methods. Results. The paper presents the results of experimental studies using kirlianography in solving problems of medicine, ecology, and the pedagogical process. To present the results of experimental studies using kirlianography in solving problems of medicine and ecology. Conclusion. The advantage of kirliography as a bioenergy-informational, innovative method is its high sensitivity and the ability to register nonspecific changes in the body at the level of pre-illness, early detection of electro physical disturbances in biosphere objects with a negative impact on environmental factors, rapid assessment of the state of the energy-informational component of water and biological fluids, determining their bioactivity.